Design and development of a portal for time of use pricing in smart grid - Khine Tun, Khine (2015)
Nowadays, the rapid development in technologies and data-centric economy expects increasing demand and good power quality from the grid. Hence, it is critical to improve the efficiency of the power system and this needs the participation from the demand side. Besides, existing flat retail electricity rate will not motivate consumers to manage their electricity usage well. In this project, a user friendly interfaced portal for Time-Of-Use (TOU) pricing for residential households and commercial buildings is developed where registered customers are able to monitor their daily consumption and electricity charges according to the TOU pricing scheme. In addition, automatic alerts will be sent to the registered customers via email indicating excess consumption to do necessary actions in load controlling when the maximum demand hits the threshold limit. Besides, with the integration of distributed generations (DG) and battery energy storage system (BESS), users can increase savings in electricity bills and reduce the carbon footprint. Therefore, the developed portal for TOU pricing in smart grid serves as an information platform for the consumers to perform the energy management as economically and environmentally as possible.